Flavonols in the Prevention of Diabetes-induced Vascular Dysfunction. Issue 6 (June 2015) - Leo, Chen-Huei; Woodman, Owen L.
Abstract : Abstract: As flavonols are present in fruits and vegetables, they are consumed in considerable amounts in the diet. There is growing evidence that the well-recognized antioxidant, anti-inflammatory, and vasorelaxant actions of flavonols may, at least in part, result from modulation of biochemical signaling pathways and kinases. It is well established that diabetes is associated with increased cardiovascular morbidity and mortality. Despite clinical management of blood glucose levels, diabetes often results in cardiovascular disease. There is good evidence that endothelial dysfunction contributes significantly to the progression of diabetic cardiovascular diseases. This review describes the biological actions of flavonols that may ameliorate adverse cardiovascular events in diabetes. We discuss evidence that flavonols may be developed as novel pharmacological agents to prevent diabetes-induced vascular dysfunction.